2020
DOI: 10.3390/ijms21124381
|View full text |Cite
|
Sign up to set email alerts
|

Preimplantation Genetic Testing: Where We Are Today

Abstract: Background: Preimplantation genetic testing (PGT) is widely used today in in-vitro fertilization (IVF) centers over the world for selecting euploid embryos for transfer and to improve clinical outcomes in terms of embryo implantation, clinical pregnancy, and live birth rates. Methods: We report the current knowledge concerning these procedures and the results from different clinical indications in which PGT is commonly applied. Results: This paper illustrates different molecular techniques used for this purpos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
42
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(43 citation statements)
references
References 191 publications
(250 reference statements)
0
42
0
1
Order By: Relevance
“…Some indicate that advanced maternal age was not seen to be correlated with a higher prevalence of mosaicism (Munné and Wells 2017;Nakhuda et al 2018). Other reports observed a significant maternal age effect on the success of mosaic embryos (Victor et al 2019;Greco et al 2020), while Coll et al (2020), found that a positive association with mosaicism showed only paternal age. Our data demonstrate meaningful differences in the maternal age distributions between disease-defined males and females, while paternal ages did not differ.…”
Section: Parental Ages Of Segmental Mosaicism Carriersmentioning
confidence: 97%
See 1 more Smart Citation
“…Some indicate that advanced maternal age was not seen to be correlated with a higher prevalence of mosaicism (Munné and Wells 2017;Nakhuda et al 2018). Other reports observed a significant maternal age effect on the success of mosaic embryos (Victor et al 2019;Greco et al 2020), while Coll et al (2020), found that a positive association with mosaicism showed only paternal age. Our data demonstrate meaningful differences in the maternal age distributions between disease-defined males and females, while paternal ages did not differ.…”
Section: Parental Ages Of Segmental Mosaicism Carriersmentioning
confidence: 97%
“…Until recently, mosaic embryos had not been considered for transfer. Greco et al (2020) were the first to demonstrate that mosaic embryos may have the potential for giving birth to healthy offspring. Among mosaic embryos, one-third of the mosaic cases were segmental mosaics (Liu et al 2017;Nakhuda et al 2018;Coll et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies provide evidence that it is worth performing preimplantation genetic testing to detect aneuploidy in embryos generated from women of advanced age, and using this procedure, the live birth rate can be increased [ 130 , 131 , 132 , 133 , 134 ]. By contrast, two other studies reported that the latter-mentioned testing method did not positively influence the live birth rate in pregnant women below the age of 35 years [ 135 , 136 ].…”
Section: Spindle Formation Disturbances and The Clinical Relevance Of...mentioning
confidence: 99%
“…This approach needs a single embryo intervention, and the zona can be targeted in a range far from the inner cell mass, decreasing its association in the biopsy method. The last approach mixes the previous techniques in which it consists of penetrating the zona when the blastocyst is completely expanded and then waiting for the TE herniation[4,5] (Greco., et al 2020). There are several molecular techniques to perform PGT-A, as shown in the table below.Molecular techniques Descriptions comprehensive chromosome screening (CCS) using array comparative genomic hybridization (aCGH) The method works through identifying alterations in the 24 chromosomes numbers and rearrangements when analysing the biopsied cells with a reference sample.…”
mentioning
confidence: 99%
“…Moreover, PGT-A aims to enhance the processes of a section of embryos for transfer and hence reduce the time to live birth(Wilding., et al 2019). On the other hand, some studies investigated how PGT-A can be cost-effective for couples attempting ART; for instance, a new study observed that IVF with PGT-A to be cost-effective for women over the age of 37 years, the study considered the exact cost estimations for all women > 37 years old and assumed that they would have received short-ening the time to pregnancy(Rubio., et al 2017) [6][7][8]. Likewise, a single-center observational-cohort study included a total of 2538 couples in the control group and 308 patients were into (PGT-A) group.…”
mentioning
confidence: 99%